2015
DOI: 10.1530/rep-14-0499
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of polycystic ovary syndrome: multifactorial assessment from the foetal stage to menopause

Abstract: Polycystic ovary syndrome (PCOS) is a multifactorial disorder that arises from interactions between genetic, environmental and intrauterine factors. Small-for-gestational-age (SGA) babies and the daughters of mothers with PCOS represent possible postnatal clinical targets for developmental programming by steroid excess. The presence of excess glucocorticoids and/or androgens during foetal organogenesis and growth might promote changes in gene expression, and these changes might be related to an increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 80 publications
0
60
0
Order By: Relevance
“…The premise of developmental origins of this syndrome is supported by the observation that girls born either small or large for gestational age may be at increased risk to manifest PCOS during reproductive life (Melo et al, 2010, Mumm et al, 2013). However, women born appropriate for gestational age can also develop PCOS, suggesting a multifactorial etiology (de Melo et al, 2015). A genetic susceptibility combined with an insult that occurs during intrauterine or early postnatal life may lead to reorganization of the neuroendocrine, ovarian, and metabolic systems that could culminate in disruptions observed in PCOS patients during adult life (Fig.…”
Section: Development Of Pcosmentioning
confidence: 99%
“…The premise of developmental origins of this syndrome is supported by the observation that girls born either small or large for gestational age may be at increased risk to manifest PCOS during reproductive life (Melo et al, 2010, Mumm et al, 2013). However, women born appropriate for gestational age can also develop PCOS, suggesting a multifactorial etiology (de Melo et al, 2015). A genetic susceptibility combined with an insult that occurs during intrauterine or early postnatal life may lead to reorganization of the neuroendocrine, ovarian, and metabolic systems that could culminate in disruptions observed in PCOS patients during adult life (Fig.…”
Section: Development Of Pcosmentioning
confidence: 99%
“…changes in gene expression due to the presence of increased steroids, mostly androgens, during fetal development, also appears to increase the risk for IR, prediabetes and T2DM in offspring of patients with PCOS. 49 Emerging data suggest that the gut microbiome might also be implicated in the pathogenesis of impaired glucose metabolism in patients with PCOS.…”
mentioning
confidence: 99%
“…Clinically, it is characterized by hyperandrogenemia, thin ovulation, and ovarian polycystic changes, often accompanied by insulin resistance and obesity [2,3]. The etiology of PCOS has not been clari ed yet, but, in recent years, more and more attention has been paid to the role of environmental and genetic factors in the occurrence and development of PCOS [4]. Family aggregation and twin studies have shown that PCOS has a strong heritable component [5].…”
Section: Introductionmentioning
confidence: 99%